Observer-Based Exponential Stability Control of T-S Fuzzy Networked Systems with Varying Communication Delays - Hejun Yao; Fangzheng Gao (Mathematics)
This paper is concerned with the problem of dynamic output feedback exponential stability control of T-S fuzzy networked control systems (NCSs) with varying communication delays. First, with consideration of varying communication delays, a new model of the networked systems is established by using the T-S fuzzy method, and a state observer is designed to estimate the unknown control disturbance. Then, a delay-dependent exponential stability criterion of closed-loop systems is derived by means of iterative technique and multiple augmented Lyapnov functionals and the linear matrix inequality (LMI) method. Furthermore, an observer-based controller is explicitly constructed to realize exponential stability control for this class of NCSs. An iterative algorithm is developed to compute the controller’s matrix by means of the Cone Complementarity Linearization Method (CCLM). Lastly, the validity and feasibility of the proposed exponential stability criterion are confirmed via a numerical simulation example.